The correlation between miR-200c and the severity of interstitial lung disease associated with different connective tissue diseases. (4th March 2017) - Jiang, Z; Tao, J-H; Zuo, T; Li, X-M; Wang, G-S; Fang, X; Xu, X-L; Li, X-P
Abstract : Objectives : To explore the correlation between microRNA (miR)-200c and the severity of interstitial lung disease (ILD) associated with connective tissue diseases (CTDs). Method : We recruited 218 patients with CTDs who were evaluated with high-resolution computed tomography (HRCT) and the pulmonary function test (PFT). Peripheral blood mononuclear cells (PBMCs) were acquired from 23 patients with systemic sclerosis (SSc), 29 with dermatomyositis/polymyositis (DM/PM), 30 with primary Sjögren's syndrome (pSS), 47 with rheumatoid arthritis (RA), and 23 normal controls to detect the expression level of miR-200c by quantitative reverse transcription polymerase chain reaction (QRT-PCR). miR-200c levels were compared among the different disease groups, between the group with ILD (CTD+ILD) and the group without ILD (CTD–ILD), and between mild and severe ILD groups. Forced vital capacity (FVC) and forced expiratory volume in 1 s (FEV1) were compared among the different CTD groups and the different CTD+ILD groups. Results : The miR-200c level in the SSc group was significantly higher than in the DM/PM, pSS, and RA groups, and the levels in the DM/PM and pSS groups were significantly higher than in the RA group. The level of miR-200c in the CTD+ILD group was significantly higher than in the CTD–ILD group, and the level in the severe ILD group was significantly higher than in the mild ILD group. FVC and FEV1 were significantly different among the different CTD groups, and among the different CTD+ILD groups. There was a negative correlation between the level of miR-200c and FVC and FEV1. Conclusions : The level of miR-200c was positively correlated with the severity of ILD, and miR-200c in PBMCs could be a biomarker of the severity of ILD in CTDs.